THE ROLE OF INTERNATIONAL COOPERATION IN THE DEVELOPMENT OF THE DIGITAL ECONOMY OF UZBEKISTAN (European Journal of Economics, Finance and Business Development, 2025)
International collaboration plays a pivotal role in the development of Uzbekistan's digital economy. As the nation strives to modernize its economic infrastructure, partnerships with global organizations, foreign governments, and multinational corporations have facilitated access to advanced technologies, expertise, and investments. This article examines the impact of international cooperation on the growth of Uzbekistan's digital economy, highlighting key initiatives and their contributions to digital transformation. The study underscores the importance of fostering cross-border alliances to overcome challenges such as technological gaps, workforce development, and regulatory frameworks. By leveraging international collaboration, Uzbekistan aims to position itself as a competitive player in the global digital economy.